Eighteenth-Century Quakerism and the Rehabilitation of James Nayler, Seventeenth-Century Radical - Bell, Erin (The journal of ecclesiastical history, 2008)
Although the first Quakers aligned history with superfluous tradition, detrimental to true appreciation of the inward voice of God, by the early eighteenth century they had produced their first histories as a defence against Anglican allegations of continued disorder and enthusiasm. At the same time, pressure to publish the collected works of James Nayler, a convicted blasphemer, proved particularly contentious. Leo Damrosch has sought to understand what Nayler thought he was doing in the 1650s; this study considers what motivated later Quakers to censor his works and accounts of his life, and demonstrates how English Friends in particular sought to revise the popular image of Quakerism by rewriting history.